If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 9 + 6x Reorder the terms: 1 + 7x = 9 + 6x Solving 1 + 7x = 9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 7x + -6x = 9 + 6x + -6x Combine like terms: 7x + -6x = 1x 1 + 1x = 9 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + 1x = 9 + 0 1 + 1x = 9 Add '-1' to each side of the equation. 1 + -1 + 1x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 9 + -1 1x = 9 + -1 Combine like terms: 9 + -1 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| Y=100+0.5(Y-200)+250+200 | | 1/2b^2+3b-27=0 | | x+10=5x+12 | | 4x+2.6=7 | | 4x+9y =0 | | Y=100+0.5(Y-200)+300+200 | | 3(7+y)+2y=8 | | 3=.25(m-4)+.25 | | 4x+11=x+29 | | (5w+9z)(5w+9z)=0 | | (5x-4y)(5x+4y)=0 | | 8x+3(0.3)=1 | | 2/3+x=3 | | 3a^2+4a-18=0 | | v+(v-30.8)+(v+23.2)=189.8 | | X-10/3+2x/5+x+10=180 | | 7(1-3y)-2y=-1 | | X-10/3+2x/5+x+10 | | 12=2(4a+2) | | 6y+3=x*x+14x+48 | | (15-2s)(15-2s)=0 | | -4x-7+8=6x+2+8 | | -8(-b)=-6 | | 3x+4(-2)=2 | | 3/3x+5/4x=27 | | -8-6=-6 | | -3x-6=5x-2 | | 16/x=9.32 | | 0.2(0.1x+0.7)=-0.2 | | 2-4y+3y=4 | | 4/5(x)-2+(1/10)x=7 | | C^2-50+23c=0 |